2019
DOI: 10.21203/rs.2.17215/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internship Programs for Undergraduate Health Informatics Students in Saudi Arabia

Abstract: Background Internship program is one of the experiential learning methods that enable students to gain practicum experience and learn from specialised people. This type of learning is a professional gateway to integrate knowledge with practical application. This study defines the state of health informatics internship programs in Saudi Arabia and examines the difference between interns and graduated students’ perceptions about the experience of health informatics internship programs in Saudi hospitals. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Nevertheless, an investigation in 2019 aimed to examine health informatics internships in Saudi Arabia. The study's findings demonstrated that the least agreed-upon statement among interns and graduates was that the internship program will improve their understanding of health informatics' roles and responsibilities in the future (Altuwayrib & Win, 2019;Gashaw, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, an investigation in 2019 aimed to examine health informatics internships in Saudi Arabia. The study's findings demonstrated that the least agreed-upon statement among interns and graduates was that the internship program will improve their understanding of health informatics' roles and responsibilities in the future (Altuwayrib & Win, 2019;Gashaw, 2019).…”
Section: Discussionmentioning
confidence: 98%